Diurnal space use and seasonal movement patterns of greater sage‐grouse in Northeastern California - Dawn M. Davis; Kerry P. Reese; Scott C. Gardner (Wildlife Society Bulletin, 2014)
ABSTRACT Greater sage‐grouse (Centrocercus urophasianus) populations have declined throughout their geographic range, are considered a candidate species under the U.S. Endangered Species Act, and are regarded as a species of special concern in California, USA. Demographic parameters have been well‐documented for this species, but populations occupying the western periphery of their range have largely remained unstudied. We examined diurnal space use and seasonal movement patterns of greater sage‐grouse in northeastern California. We collected 3,072 diurnal locations from 132 greater sage‐grouse radiomarked between 2007 and 2009. Greater sage‐grouse in our study used large areas and exhibited wide‐ranging seasonal movements. Female greater sage‐grouse sought suitable nesting habitat within 5 km of a lek; however, of the 27% (n = 20/74) of females nesting >5 km from an occupied lek site, 53% (n = 10/19) nested successfully. This suggests the proportion of nesting females located >5 km from an active lek is important for population viability in northeastern California. Moreover, the annual range of movements indicates that conserving greater sage‐grouse habitat within 5 km of active lek sites is insufficient to maintain long‐term population persistence. Larger areas of habitat are needed to conserve greater sage‐grouse in northeastern California to accommodate seasonal movements, annual variation in habitat requirements, and to maintain connectivity between lek complexes. © 2014 The Wildlife Society.